Urban Victims of Nonlethal Gun Violence: A Chicago-Centered Analysis Using the National Crime Victimization Survey - Rezey, Maribeth L. (Crime & delinquency, 2025)
This study examines city-level rates of nonlethal violence among urban residents, including whether individual- and incident-level characteristics are associated with urban residents’ risk for gun and non-gun serious violence. Specifically, we assess which Chicagoans are most at-risk for nonlethal gun victimization, which are likely to withhold these victimizations from the police, and whether they differ from residents of other large U.S. cities in these rates and reporting behaviors. We analyze pooled 1996 to 2021 National Crime Victimization Survey data and find that Chicagoans have higher risk for nonlethal gun victimization, but similar reporting rates. Overall, urbanites withheld one in three nonlethal gun crimes from police, with an injury during the incident being the most salient factor in whether it was reported.